Show Me The Rules! A User Study On Making Data Validation Rules Explicit in Spreadsheet Applications - Gava, Jessica; Vilela, Bruna; Cirilo, Elder; Adachi, Eiji (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6043, 2017)
Spreadsheet applications have become one of the most popular end-user programming environments with innumerous built-in facilities, including arithmetic, financial and statistical operations. Not surprisingly, spreadsheet applications play significant role in decision-making processes in organizations, thus making spreadsheet errors serious threats. Reports from field audits show that spreadsheet errors may cause companies to lose millions of dollars annually. One effective and simple way of helping users to avoid introducing mistakes in their spreadsheets is data validation. Indeed, most spreadsheet applications provide a wide range of built-in functions to restrict the type of the input data or the range of valid values entered into a cell. However, in most of them, the underlying design decisions governing how data input should be entered in a spreadsheet are not explicitly visible to its users. Hiding data validation rules from users may hinder the comprehensibility and the usability of a spreadsheet, thus increasing the risks of entering incorrect data input. To assist end-user programmers in explicitly expressing validation rules in spreadsheets, we propose the SpreadSheet Validation Language (SSVL). We conducted a user study to assess the effectiveness of SSVL. The results show that users using SSVL are faster and more productive in tasks involving the comprehension of data validation rules. This is a promising result suggesting that SSVL can actually improve the usability of spreadsheets.